KELAYAKAN MEDIA FILM DOKUMENTER PERILAKU MAKAN DALAM SUBMATERI ZAT MAKANAN KELAS XI SMA - Magdalena, Magdalena; Candramila, Wolly; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to determine the feasibility of documentary film medium based on the results of the eating behavior research in Sub Material of food substances in second grade of senior high school. The research used quantitative descriptive with random sampling. The tools used in this documentary film making consists of a computer and digital camera. The material in this documentary film making was the material on food substance Sub Material for second grade of senior high school. The making of this documentary film was initiated with determining the learning objective, writing synopsis, designing storyboard of the documentary film, making the script, recording the video, recording the audio for the narration (dubbing), editing and rendering, determining the validators, and validating the documentary film. The validation results of documentary film media by 3 media and material validators expert acquired the value of 3.06 for the material and 3.47 for the media aspects. The documentary medium was valid to be used as a learning medium on Sub Material of Food Substance. Keywords: Feasibility, Documentary Film, Food Substance